2017
DOI: 10.1037/pne0000096
|View full text |Cite
|
Sign up to set email alerts
|

Use of the MacAdam ellipses for psychophysical evaluation of color discrimination in chronic heavy smokers.

Abstract: Cigarette smoke is a complex chemical mixture that has health-damaging components, such as carbon monoxide, ammonia, pyridine, toluene, and nicotine. Cognitive functions have been well documented in heavy smokers, but visual perception has been less characterized. The purpose of the present study was to assess the influence of chronic heavy smoking on color discrimination. We evaluated color discrimination in healthy heavy smokers (n = 16), deprived smokers (n = 16), and healthy nonsmokers (n = 16). The partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…However, the influence of cognitive processes on visual perception is debatable and some recent studies reported no predictive effects of cognition on contrast detection (Fernandes, de Andrade, Santana, Nogueira, & Santos, 2018;Fernandes, Andrade, de Andrade, Nogueira, & Santos, 2017). As a side note, we like to mention that magno-, parvo-or koniocellular dysfunctions cannot explain visual deficits, contrary to long standing proposals and hence do not need to be discussed here (Fernandes, Almeida, Dias, Nogueira, & Santos, 2017;Herzog & Brand, 2015).…”
mentioning
confidence: 90%
“…However, the influence of cognitive processes on visual perception is debatable and some recent studies reported no predictive effects of cognition on contrast detection (Fernandes, de Andrade, Santana, Nogueira, & Santos, 2018;Fernandes, Andrade, de Andrade, Nogueira, & Santos, 2017). As a side note, we like to mention that magno-, parvo-or koniocellular dysfunctions cannot explain visual deficits, contrary to long standing proposals and hence do not need to be discussed here (Fernandes, Almeida, Dias, Nogueira, & Santos, 2017;Herzog & Brand, 2015).…”
mentioning
confidence: 90%